Neo-fused hexaphyrin: A molecular puzzle containing an N-linked pentaphyrin - Wei, P.; Zhang, K.; Li, X.; Meng, D.; Agren, H.; Ou, Z.P.; Ng, S.W.; Furuta, H.; Xie, Y. (John Wiley & Sons, 2014)
The first neo-confused hexaphyrin(1.1.1.1.1.0) was synthesized by oxidative ring closure of a hexapyrrane bearing two terminal ``confused'' pyrroles. The new compound displays a folded conformation with a short interpyrrolic C center dot center dot center dot N distance of 3.102 angstrom, and thus it readily underwent ring fusion to afford a neo-fused hexaphyrin with an unprecedented 5,5,5,7-tetracyclic ring structure. Furthermore, coordination of Cu-II triggered a ring opening/contracting reaction to afford a Cu-II complex of an N-linked pentaphyrin derivative. The roles of reactive N-C bonds in the porphyrinoid macrocycles were demonstrated.